Analysis and design of wireless power and data synchronous transfer system based on 2FSK modulation using dual‐resonant frequency. (1st July 2022) - Feng, Jing; Zhang, Jiantao; Wei, Guo; Cui, Jian; Zhu, Chunbo
Abstract: In this paper, a reconfigurable double‐sided inductor‐capacitor‐capacitor (LCC)‐based data transfer method for wireless power transfer (WPT) system is proposed. The power and the data are, respectively, transferred through the orthogonal decoupled inductive links, and thus, the interference between the power transfer link and the data transfer link can be eliminated. Dual‐resonant frequency is used to exchange data in the binary frequency‐shift keying (2FSK) modulation. The performance of the reconfigurable LCC compensation topology is explored, and the design method is presented to improve the data transfer rate and to guarantee the similar data transfer characteristics under the two different frequencies. Thus, a stable data transfer can be guaranteed irrespective of the data type. The power transfer link and data transfer link are, separately, analyzed. Together with the well‐designed parameters, 512 W power with 115.2 kbps transfer rate half‐duplex communication is obtained, and the direct current–direct current (DC–DC) efficiency reaches 80.44%. Abstract : This paper presents an orthogonal decoupled power and data synchronous transmission method for WPT. The dual‐resonant frequency of the reconfigurable double‐sided LCC‐based data transfer topology is applied to exchange data in 2FSK. Also, the design guide to guarantee the similar transfer performance under the two different carrier is also provided, and thus, a stable data transfer can be guaranteed irrespective of the kind of data.